Respon Pertumbuhan dan Hasil Kubis Bunga Terhadap Pemberian Bokashi Pupuk Kandang Ayam pada Tanah Gambut - Even Haqikhi Rizqi Dewi; Joko Purnomo; Bambang Fredickus Langai (Universitas Lambung Mangkurat, 2020)
This research aimed to determine the response of growth and yield of cauliflower on giving bokashi chicken manure on peat soils. The research was conducted at Landasan Ulin Tengah Village, Liang Anggang Sub-district, Banjarbaru District. The implementation time is 5 months from July – November 2019. This research used a Completely Randomized Design (CRD) with single factor. The treatment factors were dosage of the bokashi chicken manure (B) with five levels of treatment (i.e b0 = 0; b1 = 5; b2 = 10; b3 = 15; b4 = 20 t ha-1). Each treatment was repeated four times so that there were 20 units of trial. The variables observed are plant heigth, the number of leaves, flowering, fresh weight of plant and yield weight. The results showed that the treatment of bokashi chicken manure very significant affect the plant height parameters 20, 30, and 40 days, the number of leaves aged 30 and 40 days, flowering, fresh weight of plant and yield weight